A Study on Cybersecurity Challenges in E-learning and Database Management System - Ibrahim, Habib; Karabatak, Songul; Abdullahi, Abdullahi Abba (Institute of Electrical and Electronics Engineers Inc., 2020)
Education is gradually moving from traditional classroom-based setting to online-based. E-learning has become the topic of discussion as far as cybersecurity is concerned. E-learning as a mode of acquiring knowledge and skills through electronic means, cannot be achieved without internet technology. In other words, it depends largely on the internet technology for the sharing of ideas and information. However, the network environment is a home for hackers and the internet fraudless. As the reach of the internet expands to cover ever broader aspects of our education and social welfare, cybersecurity is the major concern when dealing with privacy, authentication, and confidentiality of user's information stored in a database server. Most often hackers release attacks designed to steal confidential data and an organization's database servers are the targets of these attacks because they are the core of any organization, storage bank. Hence, it is very important to put strong security measures in place to protect the data and information of the end-user against any malicious attack. This paper, therefore, aimed to discuss cybersecurity issues related to the e-learning management system, the significance of the e-Learning, and the Database Management System. Again the paper discusses top security issues in databases and how to lessen them. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: cybersecurity; database management system; e-learning; hackers; malicious; skills; traditional